PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA GUNUNG PICUNG, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Putri, Yulia Kania (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service aims to increase public knowledge and understandingof sharia financial planning for families in Gunung Picung Village, Pamijahan District, Bogor Regency. In this community service, activities are carried out based on the descriptive method, and for the impementation of extension activities using interview data collection techniques, documentation and observation. The results of this community service show that people’s knowledge about family financial planning is stil low. With this community service, it can be concluded that counseling to the community and Friends of Micro. Small and Medium Enterprises (UMKM) is a strategic effort to empower the community and married mothers/fathers to carry out good and orderly family financial planning, so that the community can help themselves alone.